Effect of fragmentation degree on sensory and texture attributes of cooked rice. Issue 4 (26th March 2019) - Wang, Ziyuan; Su, Huimin; Bi, Xue; Zhang, Min
Abstract: This study investigated the possibility of classified utilization of broken rice by analyzing sensory and texture attributes of cooked rice with different fragmentations. Compared with head rice, the relative concentration of volatile components in broken rice with three fragmentations (25%, 50%, 75%) increased 21%, 43% and 26%, respectively. Among them, 50% fragmentation rice sample contained the greatest amount of typical rice related aroma compounds, including heptanal, hexanal, nonanal, 1‐octen‐3‐ol, 1‐pentanol and 2‐pentylfuran. Moreover, 50% fragmentation could increase the taste intensity of fruitiness, nuttiness, toastiness and sweetness of cooked rice significantly. The hardness of cooked rice was found to be negatively related with fragmentation degree, while the stickiness and water soluble protein content were positively related with fragmentations. The results of this study suggest that suitable utilization of broken rice with 50% fragmentation has a potential to enhance desirable rice flavor and increase staple food supply. Practical applications: During rice processing, broken rice with different fragmentations will form inevitably, the composition of which is not different from head rice, but much cheaper. Broken rice with 50% fragmentation has a potential to add desirable rice flavor to cooked rice. Thus suitable utilization of broken rice could be applied to achieve high added‐value of rice milling by‐product.